Evaluation of fungicide efficacy and agronomic viability for controlling Rhizoctonia solani-induced damping-off in soybean - Vivas, Bruno Pereira de Eça; Ventura, Matheus Vinícius Abadia; Menezes Filho, Antonio Carlos Pereira de (Brazilian Journal of Science, 2025)
This study aimed to evaluate the agronomic efficacy of different fungicides applied via seed treatment for the control of Rhizoctonia solani AG-4 in soybean (Glycine max (L.) Merrill). The experiment was carried out in a greenhouse in Rio Verde, GO, Brazil, during the 2023/2024 growing season, using the Bônus 8579RSF IPRO cultivar previously inoculated with the pathogen. Nine treatments, including controls, were tested at the manufacturers’ recommended doses. The evaluated parameters included emergence, vigor, shoot height, root length, pre- and post-emergence damping-off, disease index, and product efficacy. The experimental design was completely randomized with four replications. Results showed that the treatments Fludioxonil + Metalaxyl-M + Thiabendazole and Thiophanate-methyl + Fluazinam exhibited the highest control efficacy, reducing the disease index by 73.79% and 58.39%, respectively. It is concluded that seed treatment is an effective and viable strategy for the preventive management of Rhizoctonia solani during the initial development stages of soybean cultivation.